Предмет: Математика,
автор: Ирина3221111
6*(0,4*-1 2/7-3)-4,5*(-1 2/7+2)
Ответы
Автор ответа:
0
Ответ:
-20,1
Пошаговое объяснение:
6*(0,4*-1*2/7-3)-4,5*(-1*2/7+2) = 6*(2/5-2/7-3)-4,5(-1*2/7+2) = 6*(-101/35) - 9/2 + 12/7 = -606/35 - 9/2 + 12/7 = - 202/10 = -20,1
Автор ответа:
0
Ответ:
20.1 .......................
Похожие вопросы
Предмет: Математика,
автор: ahastaskuh
Предмет: Информатика,
автор: aeqwess
Предмет: Математика,
автор: Tolikvolvo6042
Предмет: История,
автор: alyaev2005
Предмет: Литература,
автор: АнастасияВечерных